Interações entre espécies de arsênio e matéria orgânica natural: Lílian Karla de Oliveira. - - Oliveira, Lílian Karla de [UNESP] (2014)
The mobility and availability of arsenic (As) are controlled by the adsorption/precipitation from metal oxides. Therefore the organic matter (OM) present in terrestrial and aquatic environments, in junction with these oxides can also play an important role in the As cycle. In this sense, the present study evaluated the interaction between As species and MO from peat and SHA samples in natura or enriched with Fe(III) or Al(III). The results showed that enrichment Fe(III) or Al(III) in peat or SHA samples significantly increases the interactions between As and MO, with these major interactions in the samples enriched with Fe(III). The interactions were highly dependent at pH levels. The adsorption experiments in peat showed that As(III) species are not adsorbed in peat samples in natura or enriched with Al(III). Adsorption rates of As(V) range from 20.3 to 52.7 g g-1 by different samples of peat. The best fit to the results was obtained using the pseudo-second order kinetic model, and the adsorption of As(V) could be described by the Freundlich isotherm model. Desorption results showed that peat enriched with Fe(III) are effective in As(V) immobilization. In the experiments of As(V) adsorption, where redox potential values have been oscillated by purging with N2 or O2 during the process, no changes in concentrations of As, Fe and dissolved organic carbon (DOC) were observed. FTIR analysis revealed the formation of ternary complexes involving As(V) and peat enriched with metals. In complexation reactions between As and SHA, the results showed no interaction between As(III) species and SHA in natura or enriched with Al(III). Small concentrations of As(V) were complexed with the SHA in natura. The amounts of the As(III) complexing capacity were were approximately 3.6 mg g-1 C, while the As(V) values ranged from 5.2 to 6.1 mg g-1 of C. The interference of Al(III)/Fe(III) cations in the interactions of As and SHA was confirmed in reactions...